Managing for a change : how to run community development projects - Davies, Anthony; Voluntary Service Overseas (London : Intermediate Technology Publications in association with Voluntary Service Overseas, 1997)
This guide provides an insight into development project planning and management. There is advice on problem analysis, meetings, letter writing, decision making, leadership, employment of contractors and quality control.
Keywords: Community development -- Management; Economic development projects -- Management